Presunción Pater is est y su relación con la separación matrimonial en la promoción de la escuela de Postgrado en Derecho Civil y Comercial en la Universidad Nacional de la Amazonía Peruana Iquitos 2022 - Ríos Babilonia, Wilson Javier (2025)
The objective of the research was: To demonstrate that the Pater is est are related to marital separation in terms of the legal criteria of the members of the promotion of the Graduate School of Civil and Commercial Law at the National University of the Peruvian Amazon, Iquitos 2022. The research was descriptive and the design was non-experimental, cross-sectional - correlational. The population was made up of 30 participants from the promotion of the Postgraduate School in Civil and Commercial Law and the sample was made up of 100% of the population, that is, the 30. The techniques used in data collection were: The survey and the instruments were: Questionnaires. The results indicated that X2c = 0.01 < X2t = 0.103, df = 2, p < 0.05% with a relationship magnitude of 0.0182% (low relationship magnitude) between the variables, accepting the research hypothesis: Pater is est moderately related with marital separation at a level of 95% reliability in the promotion of the Postgraduate School in Civil and Commercial Law at the National University of the Peruvian Amazon, Iquitos 2022.